THU0414 Inter SPA: Sensitivity and Specifity of Autoantibodies against CD74 in Early Axial Spondyloarthritis. (15th July 2016) - Riechers, E.; Baerlecken, N.T.; Baraliakos, X.; Achilles-Mehr Bakhsh, K.; Aries, P.M.; Bannert, B.; Becker, K.; Brandt-Jürgens, J.F.; Braun, J.; Ehrenstein, B.; Euler, H.; Fleck, M.; et al.
Abstract : Background: Making the diagnosis of axial spondyloarthritis (axSpA) may be difficult. Antibodies against CD74 have been shown to be present in 2/3 of patients with long established axial SpA. Objectives: InterSpA is an international multicenter study, conducted to compare the sensitivity and specificity of anti-CD74 and HLA-B27 in patients with axSpA of recent onset. Methods: Patients between 18 and 45 years suffering from inflammatory back pain (IBP) for maximally 2 years were recruited. The presence of ankylosing spondylitis, additional inflammatory rheumatic disorders and biologic therapy were exclusion criteria. MRI of sacroiliac joint was performed in all patients; HLA-B27 was detected by genotyping and anti-CD74 using a CE certified kit of Aesku Diagnostics (Wendelsheim, Germany). The sensitivity of anti-CD74 and HLA-B27 were calculated in patients fulfilling the imaging arm of ASAS criteria, in all patients fulfilling ASAS criteria and in 100 blood donors. Both the MRI reading as well as the laboratory procedures were performed blinded. Results: 205 patients suffering from IBP were recruited. There were 40 recruiting failures. The remaining 165 patients had a mean age of 29.4 years, a mean duration of IBP of 12.6 months, 50% of the patients were female. Sacroiliitis was diagnosed by the local and an independent expert reader in 71/123 (57.7%). So far complete data sets are available of 91 patients. Of these, 16 fulfilled the ASAS criteria of axSpA by a pathologic MRI only, 40 by both MRI and presence of HLA-B27 and 20 by HLA-B27 only. The sensitivities of IgA anti-CD74, IgG anti-CD74 and HLA-B27 were 71.4%, 26.8% and 75% in the 56 axSpA patients with a pathologic MRI, 73.7%, 23.7% and 81.6% in all 76 patients fulfilling ASAS criteria, and 3%, 5% and 8% in the blood donors. The likelihood ratios are 23.8 (IgA anti-CD74), 5.4 (IgG anti-CD74) and 9.4 (HLA-B27) when considering the patients with a pathologic MRI only, and 24.6 (IgA anti-CD74), 4.7 (IgG anti-CD74) and 10.2 (HLA-B27) when considering all patients fulfilling ASAS criteria. Conclusions: Considering their specificity and sensitivity, IgA anti-CD74 is a useful addition to our diagnostic tools for axSpA. Acknowledgement: This study is funded by AbbVie Deutschland GmbH & Co. KG. AbbVie contributes to study logistics and site management. The authors determined study design, conduct of the study and the content of the publication. No payments were made to the authors for writing this manuscript. Disclosure of Interest: E. Riechers Grant/research support from: AbbVie GmbH, N. T. Baerlecken Grant/research support from: AbbVie GmbH, X. Baraliakos: None declared, K. Achilles-Mehr Bakhsh: None declared, P. M. Aries: None declared, B. Bannert: None declared, K. Becker: None declared, J. F. Brandt-Jürgens: None declared, J. Braun: None declared, B. Ehrenstein: None declared, H. Euler: None declared, M. Fleck: None declared, R. Hein: None declared, K. Karberg: None declared, L. Köhler: None declared, T. Matthias: None declared, R. Max: None declared, A. Melzer: None declared, D. Meyer-Olson: None declared, J. Rech: None declared, K. Rockwitz: None declared, M. Rudwaleit: None declared, E. Schweikhard Employee of: Aesku GmbH, J. Sieper: None declared, C. Stille: None declared, U. von Hinüber: None declared, P. Wagener: None declared, H. Weidemann: None declared, S. Zinke: None declared, T. Witte Grant/research support from: AbbVie GmbH